Au@Pt@HP1-HP2@Fe3O4 Nanoenzymatic Complexes Based on CHA Signal Amplification Strategy for Ultrasensitive SERS Detection of ctDNA in Liver Cancer - Wang X; Sheng J; Yang H; Shen K; Yao J; Qian Y; Chen G (International Journal of Nanomedicine)
Xiaoyong Wang,1,* Jinxin Sheng,1,* Haifan Yang,2,3 Kang Shen,2,3 Jie Yao,1 Yayun Qian,2,3 Gaoyang Chen4 1Department of General Surgery, Nantong Haimen People’s Hospital, Nantong, Jiangsu, People’s Republic of China; 2Institute of Translational Medicine, Medical College, Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China; 3The Key Laboratory of Syndrome Differentiation and Treatment of Gastric Cancer of the State Administration of Traditional Chinese Medicine, Yangzhou, Jiangsu, People’s Republic of China; 4Department of Oncology, The Affiliated Taizhou Second People’s Hospital of Yangzhou University, Taizhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gaoyang Chen, Department of Oncology, The Affiliated Taizhou Second People’s Hospital of Yangzhou University, Taizhou, Jiangsu, People’s Republic of China, Email taizhouchengaoyang@163.comPurpose: Early diagnosis of liver cancer requires highly sensitive detection of biomarkers. This study aims to develop a novel method for detecting circulating tumor DNA (ctDNA) in the serum of liver cancer patients, leveraging a catalytic hairpin self-assembly (CHA) signal amplification strategy combined with surface-enhanced Raman scattering (SERS) technology and nano-enzyme catalysis.Methods: We synthesized Au@Pt@HP1-HP2@Fe3O4 nano-enzyme complexes, utilizing the SERS-enhancing properties of Pt-coated Au nanoparticles (Au@Pt) and the separation-enrichment capability of Fe3O4 magnetic beads. The complexes catalyzed the oxidation of colorless TMB by H2O2 to produce blue ox-TMB, enabling quantitative detection of PIK3CA E542K mutant ctDNA. The assay’s performance was validated using gold standard qRT-PCR.Results: Under optimized conditions, the method achieved a detection limit for PIK3CA E542K as low as 4.12 aM. The assay demonstrated high sensitivity, specificity, and efficient magnetic separation, making it a robust tool for ctDNA detection.Conclusion: This study presents a highly sensitive and specific detection platform for liver cancer early diagnosis, characterized by magnetic separation and nano-enzyme catalysis. The method holds significant clinical potential for the accurate and early detection of liver cancer biomarkers.Keywords: surface-enhanced Raman scattering, nano-enzymes, circulating tumor DNA, liver cancer, catalytic hairpin self-assembly